Cadmium toxicity on seed germination and seedling growth of wheat Triticum aestivum - Maria de Fátima Souza Guilherme; Habyhabanne Maia Oliveira; Edevaldo da Silva (Acta Scientiarum. Biological Sciences, 2015)
Cadmium toxicity in seed germination and seedling growth of wheat (Triticum aestivum, var. IAC-370) is assessed. The ecotoxicological effects of six experimental concentrations of cadmium (0.03; 0.06; 0.12; 0.6; 1.2; 2.4; 4.8 mM), and control were evaluated. All assays were performed in quadruplicates with 25 seeds per replication in Petri dishes. Responses for toxic effect comprised the variables germination percentage, index of velocity of germination (IVG), length of aerial section and root of the seedlings, green and dry mass of the seedlings. Results showed that T. aestivum seeds exposed to cadmium decreased their normal germination percentage as from 0.03 mM concentration, with a 31% reduction of germination percentage and a 20% decrease in IVG. Cadmium´s inhibition effect on initial growth of seedlings influenced growth of roots and aerial part as from concentration 0.12 mM and reduced the production of green and dry mass of seedlings as from 0.06 mM. The presence and accumulation of cadmium in the soil cultivated with T. aestivum may trigger liabilities in productivity and/or viability caused by its toxicity as from 0.03mM concentrations absorbed by the plant roots.